ANALISIS PENGARUH CUTTING SPEED DAN FEEDING RATE MESIN BUBUT TERHADAP KEKASARAN PERMUKAAN BENDA KERJA DENGAN METODE ANALISIS VARIANS - Rakian Trisno Valentino Febriyano; Agung Sutrisno; Rudy Poeng (Fakultas Teknik Jurusan Teknik Mesin Universitas Sam Ratulangi, 2015)
ABSTRACT The purpose of this research is to get the influence of cutting speed variation and feeding rate variation on turning machine to work piece surface roughness. The problem in this research is how the influence of Cutting Speed and feeding rate on turning machine to work piece surface roughness with method of variance analysis. Therefore, studying the turning machine and measurement of surface roughnes with some work piece are requird. From the cutting calculation result, it is found that if cutting speed is increasing, the surface roughness is decreasing, while if feeding rate is increasing, the surface roughness is increasing. From the variance analysis with 95 % of confidence level, result of the cutting speed variation on turning machine will not give significant influence to work piece surface, and the result of feeding rate variation will give significant influence. Keyword: Cutting Speed, Feeding Rate, Turning Machine, Surface Roughness